Disease Activity-Associated Alteration of mRNA m5 C Methylation in CD4+ T Cells of Systemic Lupus Erythematosus - Guo, Gangqiang; Wang, Huijing; Shi, Xinyu; Ye, Lele; Yan, Kejing; Chen, Zhiyuan; Zhang, Huidi; Jin, Zibing; Xue, Xiangyang (Frontiers in Cell and Developmental Biology, 2020)
Epigenetic processes including RNA methylation, post-translational modifications, and noncoding RNA expression have been associated with the heritable risks of systemic lupus erythematosus (Petri et al., 2012). In this study, we aimed to explore dysregulated expression of 5-methylcytosine (m5C) in CD4+ T cells from patients with SLE and the potential function of affected mRNAs in SLE pathogenesis. mRNA methylation profiles were ascertained through chromatography-coupled triple quadrupole mass spectrometry in CD4+ T cells from two pools of patients with SLE exhibiting stable activity, two pools with moderate-to-major activity, and two pools of healthy controls (HCs). Simultaneously, mRNA methylation profiles and expression profiling were performed using RNA-Bis-Seq and RNA-Seq, respectively. Integrated mRNA methylation and mRNA expression bioinformatics analysis was comprehensively performed. mRNA methyltransferase NSUN2 expression was validated in CD4+ T cells from 27 patients with SLE and 28 HCs using real-time polymerase chain reaction and western blot analyses. Hypomethylated-mRNA profiles of NSUN2-knockdown HeLa cells and of CD4+ T cells of patients with SLE were jointly analyzed using bioinformatics. Eleven methylation modifications (including elevated Am, 3’OMeA, m1A, and m6A and decreased Ψ, m3C, m1G, m5U, and t6A levels) were detected in CD4+ T cells of patients with SLE. Additionally, decreased m5C levels albeit increased number of m5C-containing mRNAs were observed in CD4+ T cells of patients with SLE compared with that in in CD4+ T cells of HCs. m5C site distribution in mRNA transcripts was highly conserved and enriched in mRNA translation initiation sites. In particular, hypermethylated m5C or/and significantly up-regulated genes in SLE were significantly involved in immune-related and inflammatory pathways, including immune system, cytokine signaling pathway, and interferon signaling. Compared to that in HCs, NSUN2 expression was significantly lower in SLE CD4+ T cells. Notably, hypomethylated m5C genes in SLE and in NSUN2-knockdown HeLa cells revealed linkage between eukaryotic translation elongation and termination, and mRNA metabolism. Our study identified novel aberrant m5C mRNAs relevant to critical immune pathways in CD4+ T cells from patients with SLE. These data provide valuable perspectives for future studies of the multifunctionality and post-transcriptional significance of mRNA m5C modification in SLE.